A fluorene-containing water-soluble poly(p-phenyleneethynylene) derivative: Highly fluorescent and sensitive conjugated polymer with minor aggregation in aqueous solution - Huang, Y.-Q. (2014)
10.1016/j.polymer.2006.04.038